(untitled) (Boston, Mass., 2002)
The original text that set the standard for introduction to art courses across the country, Art Fundamentals has guided generations of students through the essential elements of art as well as the rich and varied history of their uses. This book has been carefully revised to expand and clarify concepts throughout the text, while adding new material on developing ideas, critical thinking, and time and motion.
Keywords: Art,Mỹ thuật; Technique,Kỹ thuật